Pricing Asian Options on BBCA Stocks: A Binomial and Black-Scholes Approach - Antoro, Srava Chrisdes; Irsan, Maria Yus Trinity (President University, 2025)
This paper aims to evaluate the pricing of Asian options using two widely recognized methods: the Binomial Option Pricing Model and the Black-Scholes Model. Asian options are a form of exotic options where the payoff depends on the average price of the underlying asset over a specified period, reducing the impact of market volatility compared to standard European or American options. The research focuses on BBCA (Bank Central Asia) stock data over a two-month period from September to November 2024. The study uses the arithmetic average for the binomial model and the geometric average for the Black-Scholes model. Essential financial parameters such as risk-free interest rate, volatility, and strike prices are determined based on real market data and standard assumptions. The binomial model offers a numerical approach through discrete time intervals, while the Black-Scholes model provides a closed-form analytical solution. Results show that the call option prices from the binomial and Black-Scholes models are 1,228.79 and 1,272.02 respectively, with a Mean Absolute Percentage Error (MAPE) of 3.52%. For the put options, the binomial and Black-Scholes prices are 1,754.46 and 1,711.21, respectively, with a MAPE of 2.46%. These low error rates suggest that both models can accurately estimate Asian option values. The study concludes that both the binomial and Black-Scholes models are effective tools for pricing Asian options on BBCA stock, offering comparable results with minimal deviation. This finding supports the use of these models in financial decision-making for exotic options in the Indonesian market